Review of Christina Koulouri, Φουστανέλες και χλαμύδες: Ιστορική μνήμη και εθνική ταυτότητα, 1821–1930 : [Fustanellas and chlamydes: Historical memory and national identity, 1821–1930] - Gazi, Effi (Historein, 2022)
Review of Christina Koulouri, Φουστανέλες και Χλαμύδες: Ιστορική μνήμη και εθνική ταυτότητα, 1821–1930 [Fustanellas and chlamydes: Historical memory and national identity, 1821–1930]. Athens: Alexandria, 2020. 607 pp. To view the full text, click on the button "HTML".